A systematic review and metaethnography to identify how effective, cost-effective, accessible and acceptable self-management support interventions are for men with long-term conditions (SELF-MAN) - Paul Galdas; Zoe Darwin; Jennifer Fell; Lisa Kidd; Peter Bower; Christian Blickem; Kerri McPherson; Kate Hunt; Simon Gilbody; Gerry Richardson (National Institute for Health Research, 2015)
Background: Self-management support interventions can improve health outcomes, but their impact is limited by the numbers of patients able or willing to access them. Men's attendance at, and engagement with, self-management support appears suboptimal despite their increased risk of developing serious and disabling long-term conditions (LTCs). Objectives: To assess the effectiveness, cost-effectiveness, accessibility and acceptability of self-management support interventions in men with LTCs. Methods: A quantitative systematic review with meta-analysis and a qualitative review using a metaethnography approach. The findings of the two reviews were integrated in parallel synthesis. Data sources: In the quantitative review, the Cochrane Database of Systematic Reviews was searched to identify published reviews of self-management support interventions. Relevant reviews were screened to identify randomised controlled trials (RCTs) of self-management support interventions conducted in men alone, or which analysed the effects of interventions by gender. In the qualitative review, the databases Cumulative Index to Nursing and Allied Health Literature, EMBASE, Medical Literature Analysis and Retrieval System Online, PsycINFO and Social Science Citation Index (July 2013) were searched from inception to July 2013. Review methods: In the quantitative review, data on relevant outcomes, patient populations, intervention type and study quality were extracted. Quality appraisal was conducted independently by two reviewers using the Cochrane risk of bias tool. Meta-analysis was conducted to compare the effects of interventions in male, female and mixed-sex groups. In the metaethnography, study details, participant quotes (first-order constructs) and study authors' themes/concepts (second-order constructs) were extracted. Quality appraisal was conducted independently by two reviewers using the Critical Appraisal Skills Programme tool. Data were synthesised according to a metaethnography approach. Third-order interpretations/constructs were derived from the extracted data and integrated to generate a 'line-of-argument' synthesis. Results: Forty RCTs of self-management support interventions in male-only samples, and 20 RCTs where an analysis by gender was reported, were included in the quantitative review. Meta-analysis suggested that interventions including physical activity, education and peer support have a positive impact on quality of life in men, and that men may derive more benefit than women from them, but there is currently insufficient evidence to draw definitive conclusions. Thirty-eight qualitative studies relevant to men's experiences of, and perceptions of, self-management support were included in the qualitative review. The metaethnography identified four concepts: (1) need for purpose; (2) trusted environments; (3) value of peers; and (4) becoming an expert. Findings indicated that men may feel less comfortable engaging in support if it is perceived to be incongruous with valued aspects of masculine identities. Men may find support interventions more attractive when they have a clear purpose, are action-oriented and offer practical strategies that can be integrated into daily life. Support delivered in an environment that offers a sense of shared understanding can be particularly appealing to some men. Conclusions: Health professionals and those involved in designing interventions may wish to consider whether or not certain components (e.g. physical activity, education, peer support) are particularly effective in men, although more research is needed to fully determine and explore this. Interventions are most likely to be accessible and acceptable to men when working with, not against, valued aspects of masculine identities. Study registration: This study is registered as PROSPERO CRD42013005394. Funding: The National Institute for Health Research Health Services and Delivery Research programme.